Investigation of parameters for fault detection of worm gear box using denoise vibration signature - Barshikar, Raghavendra; Baviskar, Prasad; Ghongade, Harshvardhan; Dond, Dipak; Bhadre, Anjali (Zielona Góra: Uniwersytet Zielonogórski)
In industrial applications, worm gearboxes are a key element. In a worm gearbox, as the material of a worm wheel is softer than that of a worm screw, the worm wheel gear is vulnerable to failure through various modes like pitting, wearing out, or tooth breakage during the sliding process. Due to this, it is essential to monitor the failure of the worm wheel gear of the worm gearbox, and it has gained importance for the diagnosis of faults in gearboxes.
Keywords: sliding process; faulty worm wheel; faulty worm wheel bearing; frequency domain; vibration signature